Nede på jorden . Blue Collar White Christmas - Kestner, Max (Lynx Media A/S ; Koncern TV-OG Filmproduktion APS, 2004)
Duration: 01:22:00 December 2001. The workers at the lifeboat factory Viking are preparing for the coming Christmas holiday when news arrives that Viking is to open a new factory in Thailand. Redundancy looms. Throughout the Christmas month we follow the four main characters - Diana, Lotte, Kragelund and Tobiesen. While notification of who is to be laid off draws closer, the air becomes thick with rumours and predictions. Life continues nevertheless. "Blue Collar White Christmas" is a series of humorous everyday chronicles dealing with the fear and necessity of change.